Intertwined narratives in higher education - How do we constitute ourselves as a community and collaboratively produce emancipatory knowledge about arts-based research? - Ana Serra Rocha; Ana Paula Caetano; Ana Luisa Paz (Universidade Federal do Norte do Tocantins, 2021)
This article sets up a collaborative narrative of three elements from the Group Study on Participatory and Artistic Processes in Research and Education (GEPPAIE), composed of researchers in academic and professional development (professors, doctoral and master's students in Education areas). It begins with a question: how have we experienced, as a higher education study group, our meeting spaces for the production of emancipatory knowledge about research, especially about arts-based research? This question unfolds into others and drives us to what has already been produced collectively, but also boosts the new writings and reflections in this text. It is also part of Ana Serra Rocha's PhD, focused on the problematization of The book's experience as a place of epistemological reflection in artistic education, aiming at a broader reflection in the field of artistic education and in doctoral studies. It speculates on the participatory processes of collaborative creation and on some issues that have been debated at GEPPAIE, namely of a relational and methodological nature, with a view to (des/re)construction of knowledge and its forms of written and visual representation.